1981
DOI: 10.1146/annurev.me.32.020181.001253
|View full text |Cite
|
Sign up to set email alerts
|

The Problem of Obesity

Abstract: In view of the conflicting data, the patent cultural biases under which we labor, and the possible harmful effects of therapy, it seems best that physicians examine the problems of obesity with the same keen scepticism and science they apply to other unsettled issues. To treat disease in the obese is obviously good. To treat simple obesity as a disease may be another matter entirely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…a failure rate at 2 years as high as 70% (9). Stunkard reported that only 25% of the patients lost 10 kg (23) and Fitzgerald reached similar conclusions in long-term studies (7). Very low calorie diets (VLCD) have been tried, but weight losses, although rapidly obtained, were seldom maintained on a long-term basis (25).…”
Section: Side Effectsmentioning
confidence: 97%
“…a failure rate at 2 years as high as 70% (9). Stunkard reported that only 25% of the patients lost 10 kg (23) and Fitzgerald reached similar conclusions in long-term studies (7). Very low calorie diets (VLCD) have been tried, but weight losses, although rapidly obtained, were seldom maintained on a long-term basis (25).…”
Section: Side Effectsmentioning
confidence: 97%
“…In general, it would seem plausible that healthy body weights, like other physical attributes, are distributed normally in the population. Body weight appears to be homeostatically regulated around a "set point" which means that, for some, obesity is a natural and possibly healthy condition (Fitzgerald, 1981;Keesey, 1980;Nisbett, 1972). The weight history of bulimic patients not only indicates that many of them are highly prone to obesity (and probably a higher than average "set point" for body weight) but also that they have at one time lost as much body weight as found in anorexia nervosa yet they have never been emaciated.…”
Section: Unrealistic Goal Weights In Treatmentmentioning
confidence: 99%
“…To treat simple obesity as a disease may be another matter entirely'. 25 We need to focus on the medical and emotional needs of the obese patient rather than on the size of the patient. This may help to improve the uncomfortable and potentially harmful relationships between the obese patient and the health care provider.…”
Section: Discussionmentioning
confidence: 99%